Thermal-Moisture Dynamics at Different Underlying Surfaces in Permafrost Regions of the Central Tibetan Plateau by considering the Effect of Rainfall. (28th July 2022) - Lei, Bingbing; Wang, Bin; Zhang, Mingli; Zhou, Zhixiong; Li, Guang; Yue, Guodong
Abstract : The Qinghai-Tibetan Plateau (QTP) has undergone an increase in rainfall and a drastic alteration in the moisture-heat regime in active layers and engineering. To investigate the water and heat responses of natural ground and engineering to rainfall, the differences in energy on the ground surface and the thermal-moisture dynamics of different permafrost underlying surfaces were discussed. Based on the meteorological data in 2013 observed at the Beiluhe observation station, three types of underlying surfaces (i.e., natural ground, asphalt pavement, and gravel pavement) were selected to compare the differences in energy balance at the ground surface, water-energy transport process, and coupling mechanism in active layers under rainfall conditions by a coupled water vapor-heat model of the unsaturated frozen soil. The results show that the asphalt pavement greatly increases the surface net radiation and soil surface heat flux, decreases the surface evaporation latent heat, and cuts off the moisture migration between the atmosphere and the active layer. The gravel pavement significantly increases the surface evaporation latent heat to lower the soil surface heat flux, and the amount of moisture in shallow soil is strongly influenced by rainfall and evaporation. Therefore, the moisture migration and accumulation under the asphalt pavement are dominated by the water vapor flux under thermal gradients, whereas the liquid water under the water potential gradients is the major source of moisture migration under the gravel pavement. The heat transfer in the shallow active layer is dominated by heat conduction. The effect of heat conduction, water vapor migration, and phase transition on the soil temperature is evident for the asphalt pavement, while the impact of liquid water migration on the shallow soil temperature for the gravel pavement is significant in the thawing period. As a result, the soil temperature relationship between different underlying surfaces is asphalt pavement>gravel pavement>natural ground. The thickness of the active layer gradually decreases. Although rainfall infiltration promotes the liquid water convection of the gravel pavement, the decrease in heat flux is less than the increase in thermal conductivity. In general, the construction of asphalt pavement and gravel pavement accelerates the degradation of permafrost. The results can provide theoretical and simulated guidance for the stability prediction and analysis of various underlying surfaces in the central QTP where rainfall is increasing.